1993
DOI: 10.1159/000313032
|View full text |Cite
|
Sign up to set email alerts
|

Botulinumtoxintherapie beim idiopathischen Torticollis spasmodicus

Abstract: Das als Verursacher des Botulismus bekannte Toxin des Clostridium botulinum ist das stÄrkste bekannte Gift. Durch Blockade der AcetylcholinausschÜttung in den neuromuskulÄren Synapsenspalt fÜhrt es zu chemischer Denervierung der Muskulatur. In geeigneter VerdÜnnung kommt es bei intramuskulÄrer Injektion nur zu lokaler Wirkung, die zur Therapie fokaler Dystonien eingesetzt wird. Die Autoren berichten Über ihre ersten Erfahrungen bei der Behandlung des Torticollis spasmodicus. Die Methode der elektromyographisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Side effects were not reported by the patients. As opposed to our experiences with toxin treatment of muscular dyskinesias, 14‐17 the effect of BOTOX therapy in persons with Frey's syndrome was much extended. The subjective reports of 18 patients (with or without recurrence of gustatory sweating [one patient was lost to follow‐up]) showed that the full effect of the first injection lasted for a period ranging from 11 to 27 months (mean, 17.3 months).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Side effects were not reported by the patients. As opposed to our experiences with toxin treatment of muscular dyskinesias, 14‐17 the effect of BOTOX therapy in persons with Frey's syndrome was much extended. The subjective reports of 18 patients (with or without recurrence of gustatory sweating [one patient was lost to follow‐up]) showed that the full effect of the first injection lasted for a period ranging from 11 to 27 months (mean, 17.3 months).…”
Section: Resultsmentioning
confidence: 78%
“…Based on our experience with the application of the toxin to treat movement disorders of craniofacial muscles, 14‐17 we were surprised to notice the long periods during which BOTOX was sufficient in controlling Frey's syndrome. Similar observations were made by other authors 12 who dealt with single cases.…”
Section: Discussionmentioning
confidence: 99%